iPod & iTunes for Dummies 3rd Edition - Bove, Tony (Wiley Publishing, 2011)
Imagine running your daily errands while listening to songs from five different albums, or creating a party mix that lasts all night long, or catching the news briefings while walking to class. Whether we’re commuting to work or heading off on a vacation, the iPod has revolutionized how we listen to music. Never before has a device with such capacity been so easy to carry that even the largest model weighs less than two CD jewel cases. IPod & iTunes for Dummies offers a comprehensive but friendly guide to this new technology that is sweeping the world.